We are not the same people we used to be: an exploration of family biographical narratives and identity change following traumatic brain injury - Whiffin, Charlotte Jane; Ellis-Hill, Caroline; Bailey, Christopher; Jarrett, Nikki; Hutchinson, P.J. (Taylor & Francis, 2017)
Subjective changes are increasingly recognised as important in recovery and rehabilitation following traumatic brain injury. Accumulation of subjective changes over time has led many to examine the question of “continuity of self” post-injury. Vacillation between feeling the same and different is common and often at odds with the medical narrative preparing families for permanent change. This position of ambiguity was examined in a qualitative narrative study. The aim of this paper is to describe the narrative structures used by uninjured members of a family to understand change. These changes relate primarily, to their perspective of whether and how the injured person had changed, but also secondarily to whether and why they themselves felt they had changed in the first year post-injury. Nine uninjured family members from three families took part in three unstructured interviews during the first twelve months post-injury. In-depth narrative analysis showed family members used biographical attendance; biographical disruption; biographical continuity; and biographical reconstruction to understand change. Drawing on these findings it is argued that concentrating on a narrative of change is too limiting and that engaging in biographical narratives may help humanise care provided to injured individuals and their families. Implications for research and practice are discussed.